Holocene flood records and human impacts implied from the pollen evidence in the Daming area, North China Plain - Yang, Jinsong; Liu, Linjing; Roberts, Harry; Liu, Zhe; Song, Lei; Zhang, Peng (Frontiers in Earth Science, 2024)
Understanding the environmental significance of pollen and spores in alluvial plains is important for stratigraphic correlation and paleoenvironmental reconstruction. This paper presents palynological data in the North China Plain and explores their relationship with paleoflood records and human impacts since the Holocene. Our data reveal that pollen concentration and pollen assemblage vary in flood deposits (including overbank deposits and slackwater deposits) and inter-flood deposits (including sandy soils and lacustrine deposits). Flood deposits have higher fern percentages (28.6%) and lower herbaceous percentages (14.8%) compared to inter-flood deposits, though slackwater deposits share similar pollen concentrations and assemblages with sandy soils. Notably, overbank deposits are characterized by pollen-poor zones and aggregation of deteriorated pollen grains, especially in Unit III (755-385 cm, ca. 3.2-2.2 ka) and Unit V (190-0 cm, after ca. 0.6 ka). These findings suggest that overbank deposits correspond to strengthened hydrodynamic conditions at the flood-peak stage.Furthermore, the indicative pollen and spores provide compelling evidence for intensifying human impact on the North China Plain since the late Holocene. An aggregation of Selaginella sinensis at the depth of 640-610 cm indicates deforestation in the uplands since ca. 2.9 ka. Similarly, a sharp increase in Malvaceae percentage at the depth of 285-215 supports historical records of initial cotton planting in the Tang Dynasty (ca. 1.4-1.1 ka). The study underscores the value of palynological analysis for reconstructing paleoenvironment and human-environment interactions, providing a robust framework for understanding landscape evolution in the North China Plain.